Роль соціального підприємництва в інвестиційному розвитку регіону - Задорожня, Л. М.; Zadorozhnia, L (ЛА НАУ, 2022)
У статті розглянуто сутність та значення соціального підприємництва, як складової соціально-економічного розвитку регіону. Проаналізовано доступність фінансових інструментів розвитку соціального підприємництва. Особливо виділено, краудфандинг, мезонінне фінансування, імпакт-інвестування, гібридний капітал. Визначено важливість розвитку інструментів інвестування із заниженими фінансовими вимогами. Теоретична значимість отриманих результатів полягає у розширенні теоретико-методологічних положень дослідження соціального підприємництва щодо систематизації фінансових інструментів, що використовуються в міжнародній практиці. Практична значимість результатів дослідження полягає у виявленні доступних фінансових джерел, які застосовуються у вітчизняній практиці. The essence and importance of social entrepreneurship as a component of the region’s socio-economic development and the financial instruments’ availability for the social entrepreneurship’s development are revealed. Especially highlighted are crowdfunding, mezzanine financing, impact investment, hybrid financing. The importance of investment instruments development with undervalued financial requirements is determined. The social enterprise’ development a is closely related to financial and material provision, which improves the socio-economic and investment development of the region. The purpose of business’ social investment is to increase the investment attractiveness of the company and the region by increasing human capital and minimizing social risks. In this aspect, the social entrepreneurship ability to attract investments and achieve social effect from the enterprise’s activities is especially important. Social entrepreneurship in Ukraine has already established itself as one of the effective mechanisms for solving socially significant problems: in particular, through creating jobs for representatives of population vulnerable groups and investing income in new social initiatives, as well as attracting investments to the region of investment location. The union role of the now lies in combining the efforts of existing Ukrainian social enterprises from various spheres to support, popularize and scale their activities. And the association’s absolute goal is the formation and development of social enterprises in Ukraine as a social economy realization form. It is determined that social entrepreneurship within the region is aimed at solving the region social problems, applying innovative approaches to increase the social effect, partial self-sufficiency and financial stability, spreading positive experience to increase social impact, the social entrepreneur ability to see the market shortcomings, find opportunities, accumulate resources, develop new solutions that have a long-term positive social impact on society as a whole. Social entrepreneurship plays an important role in attracting investment funds to the region development. It is proposed to apply intact sources of funding for social entrepreneurship for the policy of socio-economic and investment development of regions. One such source is crowdfunding, impact investment, mezzanine capital. There are new funding sources for social entrepreneurship, which involve investing in various ways in social entrepreneurship to achieve a social effect.
The ability of territorial communities to financially provide investment development of the region
Keywords: соціальне підприємництво; інвестиції; гранти; державна підтримка; фінансове забезпечення; краудфандинг; імпакт-інвестування; мезонінний капітал; social entrepreneurship; investment; grands; public support; financial security; crowdfunding; impact investment; mezzanine capital